Long-term ¹³⁷Cs activity monitoring of mushrooms in forest ecosystems of the Czech Republic - Škrkal, J; Rulík, P; Fantínová, K; Burianová, J; Helebrant, J (Radiation protection dosimetry, 2013)
This paper reports on results of activity mass concentration analyses performed in various forest mushrooms in the Czech Republic within 1986 and 2011. The estimated effective half-life of (137)Cs and its environmental half-life (i.e. the effective half-life minus the effect of physical decay) were found to be 5.6 ± 0.6 and 6.9 ± 0.7 y, respectively. Non-homogeneity in (137)Cs surface contamination over the country's territory and fungus species-based (137)Cs accumulation capacity then account for a span of up to 4 orders of magnitude in activity mass concentrations measured each year after the Chernobyl accident. The highest geometric activity mass concentration (Bq kg(-1) of dry weight) means of (137)Cs (obtained from samples between years 2004 and 2011) were measured in Suillaceae (1050 Bq kg(-1)) and Boletus badius (930 Bq kg(-1)), the lowest in Agaricus (1 Bq kg(-1)). The geometric mean of all mushrooms amounted to 230 Bq kg(-1), being 440 Bq kg(-1) in Boletales, 150 Bq kg(-1) in Russulales and 21 Bq kg(-1) in Agaricales. Geometric standard deviation levels were generally high. The highest Cs accumulation capacity was observed in Boletales (namely in Suillaceae), while the lowest in Agaricales, being over 3 orders of magnitude lower than in Suillaceae.
Keywords: Regression Analysis; Radiation Monitoring; Chernobyl Nuclear Accident; radioaktivní kontaminace potravin; Food Contamination, Radioactive; Food Contamination; Radiometry; radioaktivní látky znečišťující půdu; regresní analýza; radiometrie; černobylská havárie; stromy; Cesium Radioisotopes; Soil Pollutants, Radioactive; kontaminace potravin; monitorování radiace; Plant Roots; těžké kovy; Czech Republic; Agaricales; radioizotopy cesia; ekosystém; Česká republika; vystavení vlivu životního prostředí; Ecosystem; Radiation Dosage; Trees; kořeny rostlin; dávka záření; Environmental Exposure; Metals, Heavy